Epidemiology of placenta previa: 10 years analysis in Bamako’s district - Théra, Tiounkani; Tégueté, Ibrahim; Kouma, Aminata; Diallo, Bocary; Bocoum, Amadou; Diallo, Bocary; Moukoro, Niani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The obstetrical haemorrhage constitutes the first cause of mother death, among the causes of these haemorrhages: the placenta previa. That is why we initiated this study for determine epidemiology of placenta previa in our service. The aim objective of this study was to determine the evolution and epidemiology of the placenta previa in our department. Methods: It was a cross-sectional and comparative study of 10 consecutive years. We compared two groups: with and without placenta previa. We performed a multivariate analysis using the logistic regression model as well as the Odds Ratio and its 95% confidence interval. Results: We recorded 504 cases of placenta previa among 30323 deliveries (1.7%). Age, parity and previous placenta praevia have been the recovered risk factors (p <0.001). Among the studied pathologies only placental abruption was strongly associated with placenta previa (p <0.001). However, there were no differences between the two groups according to rates of endometritis, postpartum haemorrhage and maternal death (p >0.05). Indeed, there was a significantly higher incidence of stillbirths, Apgar score <7, transfer of new-borns and small birth weights in the placenta previa group (p <0.001). Conclusions: The most significant rick factors associated with placenta previa are high maternal age, high parity and previous placenta previa, caesarean section and abortion.